MORINGA OLEIFERA, FUNCTIONAL INGREDIENT: NUTRITIONAL PROPERTIES AND HEALTH BENEFITS - PETRONELA-ELENA BURUIANA; ROXANA FILIP; VALENTINA AMARITEI; ROXANA-ELENA GHEORGHITA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Moringa oleifera is a tropical plant that provides various nutritional benefits in nutrition and medicine. It is a popular ingredient in fortified staple foods due to its antioxidant, anti-inflammatory, and anticarcinogenic properties. This study aims to assess the acceptability of the plant among students and its perceived properties. Thus, 44 subjects, divided into two groups (22 in each group) were included in this study. For ten days, each group consumed 5 or 10 grams of moringa per day. Throughout the study, the subjects completed two validated questionnaires: the first one was distributed before the consumption and the second questionnaire after the intended period. The results obtained at the end of the study showed that both groups of consumers noticed beneficial effects on physical well-being and intellectual activity. However, people who consumed 10 g of moringa experienced more noticeable effects due to its powerful effect on concentration, well-being and the elimination of factors that cause fatigue, compared to the consumption of 5 g of moringa, where the majority of respondents stated that they did not feel any effect due to the low dose ingested.